Strategies for developing Arabic language skills in teachers who aren’t specialized in it - Al-Qahtani, Maleeha Mohammed; Zahed, Manal Abdalla (Journal of Educational and Psychological Sciences, 2020)
The current study aimed to build a training program that develops the language skills of teachers who are not specialized in the Arabic language, and which exploratory study conducted by the two researchers revealed the weakness of this group of teachers in practicing the four language skills (listening, speaking, reading, writing) through a test in Language skills that was applied to a sample consisting of (48) male and female teachers in the three academic stages, consisting of (30) singles. The test results reflected the marked weakness, which confirms the need to develop Arabic language skills among teachers who are not specialized in them, hence the need to prepare a training program for the development of The skills of teachers who are not specialized in the Arabic language concerning the four language skills and the importance of the uses of skills development strategies for this program to achieve its goals, the program was designed to include five training units and be presented in (25) training sessions, the program was judged and adjusted, and the study ended with several recommendations including: The importance of applying the language skills development program to teachers who are not specialized in the Arabic language and monitoring the results of its application and training trainee teachers - who are not specialized in the Arabic language - in teacher preparation programs in colleges of education on the language skills development program and reviewing teacher training programs - in all disciplines - and enriching it with language skills development programs.